Les interrogatives dites rhétoriques au prisme de la théorie d’Antoine Culioli - Bénédicte Guillaume (Anglophonia)
This paper focuses on the so-called rhetorical interrogatives in English, in order to show how the tools of Antoine Culioli’s Theory of Enunciative and Predicative Operations (TEPO) can help to improve their description and characterisation. First, I discuss some definitions and criteria traditionally highlighted to identify rhetorical interrogatives, which are syntactically ambiguous with standard interrogatives, and also examine the way in which A. Culioli defines the interrogative modality as well as the operation of scanning, which are closely intertwined with each other. A typology of the rhetorical interrogatives in English, comprising three main categories, is then put forward. The common, factor between these categories is the fact that the scanning operation normally triggered by the recourse to a subject / auxiliary (or subject / verb) inversion, or the presence of a WH- marker, is prevented insofar as the speaker has already selected an answer.My typology is thus based on three distinct ways of providing an outlet for the scanning operation brought about by the recourse to interrogative markers, which account for the differences between each of the categories postulated. These various outcomes are pre-constructed by the speaker, so that the addressee should not voice their opinion, despite their apparent inclusion by means of the interrogative form. I also examine some examples in which such a strategy is ultimately undermined by the addressee, who feels free to express their opinion, despite the attempt by the speaker to suppress their point of view. This study is based on a personal corpus of unsolicited attested examples of British or American English, taken from novels or from recent films and series.